Assessing carbon sequestration of silvopastoral tropical landscapes using optical remote sensing and field measurements. Issue 5 (3rd September 2018) - Schneider, Laura C.; Lerner, Amy M.; McGroddy, Megan; Rudel, Thomas
ABSTRACT: This research assesses the potential of using high-resolution optical RS data and traditional field inventory to estimate carbon stocks in silvopastoral systems. We compare field data in the Macas region of the Ecuadorian Amazon with high-resolution RS data. Aboveground estimates of carbon were calculated using the field data. Tree cover was obtained through segmentation analysis of RS data. Results show 45% of the area in the study region is covered by trees and the rest is either pasture or areas cleared for new pastures. Field data shows a statistically significant positive correlation with percentage canopy cover estimated by segmentation analysis (R = 0.52), compared to a lower correlation with RS measures of NDVI (R = 0.11). In this study the amount of carbon stored in aboveground biomass ranges from 20 T/ha to 28 T/ha. The study shows how to estimate landscape variability in carbon storage, moving up in scale from ecological transects to farms.